JAEPL, Vol. 10, Winter 2004-2005 - Kristie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
Essays Lynn Z. Bloom. The Seven Deadly Virtues. The university stifles most creative writers except the most intrepid—even reckless, the good along with the bad—in the process of teaching them to write according to the conventions of the academy in general, and their specific disciplines in particular. David L. Wallace. Shallow Literacy, Timid Teaching, and Cultural Impotence. Any attempt to move to a deeper notion of literacy in our theory and pedagogy must—among other things—involve us facing our own self interest and expecting disruption in our own classrooms, departments, and universities. Roben Torosyan. Listening: Beyond Telling to 'Being' What We Want To Teach. In response to a culture of polarized argument, this paper shows a way to provide people with practice at deep listening and understanding. The author examines ways in which self-disclosure about problems of dialog may be an ideal means for teachers or leaders to show people alternate ways of being in the world of meaning making. Patricia Webb and Zach Waggoner. Analyzing Dominate Cultural Narratives of Religious Plurlaism: A Study of Oprah.com. This essay analyzes Oprah.com, the website for multimedia mogul Oprah Winfrey, to examine the tensions between dominate religious ideologies and pluralism in America. Matthew I. Feinberg. Critical Geography and the Real World in First-Year Writing Classrooms. By helping students confront the ideologies that shape their physical and cultural experiences, critical geography in first year writing classrooms may be one means of collapsing the perceived distance between the classroom and the "real world." Hildy Miller. Image into Word: Glimpses of Mental Images in Writers Writing. This essay uses thought samples and interviews to show ways writers use mental imagery in non-creative writing task. Ed Comber. Critical Thinking Skills and Emotional-Response Discourse: Merging the Affective and Cognitive in Student-Authored Texts through Taxonomy Usage. This essay discusses a taxonomy designed to help students identify emotive-response discourse in their evolving texts, a process that joins emotion and cognitive to foster critical thinking. Helen Walker. Connecting. JoAnne Katzmarek—Thoughts Like Flying Grouse Steven L. VanderStaay—I'm With You, Huck Irwin Ramirez Leopando—A Moment of Connections Christopher Sweet—The Brightening Glance Howard Wolf—Personal Teaching Reviews W. Keith Duffy. Memoirs of Soul: Writing your Spiritual Autobiography. (Nan Phifer, 2002). Elizabeth Vander Lei. A Communion of Friendship: Literacy, Spiritual Practice, and Women in Recovery. (Beth Daniel, 2003). Marian MacCurdy. Writing To Save Your Life. (Michele Weldon, 2001).